Equine Rhinosporidiosis in United Kingdom - Gail Leeming; Ken C. Smith; Mark E. Bestbier; Annalisa Barrelet; Anja Kipar (Emerging Infectious Diseases, 2007)
We report 4 cases of equine rhinosporidiosis in the United Kingdom. These cases provide evidence of spread of infectious agents from rhinosporidiosis-endemic areas to nonendemic areas by increased international movement of livestock. Surveillance should continue for this infective agent of potential relevance for numerous species, including humans.